Linda Chisholm, Between Worlds: German Missionaries and the Transition from Mission to Bantu Education in South Africa (Historia, 2021)
This is an ambitious book which focuses on the period from the inter-war years to theimplementation of Bantu Education in the early 1950s, although in passing it touches onthe entire colonial period that dates back to the 1800s. Chisholm’s work reveals themany ways in which the unique historical beginnings of western education and theimplementation of Bantu Education in South Africa were more complex andcomplicated than simply a racial analysis of the white colonizer conquering andsocializing the African through education. In this book, Chisholm situates the mission inits broader Lutheran context and discusses differences between them over theireducational politics. She further explores how power relations shifted between themission, the state, and communities and how the mission’s influence was gradually anddifferentially eroded in Natal and the Transvaal. Finally, she examines the politics ofcontinuities and changes in curricular, medium of instruction and textbooks in schoolsand teacher training.
Keywords: Linda Chisholm; Bantu Education; South Africa; education; German Mission Schools